2017
DOI: 10.1177/1179546817746632
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Echocardiographic Predictors of Arrhythmias Detected With 24-Hour Holter Electrocardiography Among Hypertensive Heart Failure Patients in Nigeria

Abstract: Background:Hypertensive heart failure (HHF) is the commonest form of heart failure in Nigeria. There is paucity of data in Nigeria on 24-hour Holter electrocardiography (24-HHECG) and important predictors of arrhythmias among HHF patients.Objectives:To determine the 24-HHECG characteristics among HHF patients. To determine the clinical and echocardiographic predictors of arrhythmias detected using 24-HHECG among HHF patients.Methods:A total of 100 HHF patients as well as 50 age-matched and sex-matched apparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Antenatally detected arrhythmias allowed prompt and early referral to our tertiary care center, preventing further deterioration. This study has shown that a high percentage of ECG detected arrhythmias have significant echocardiography and Doppler findings, similar to a study by Mene-Afejuku et al (12). Thus, also warranting that all detected arrhythmias be advised for an echocardiography and colour Doppler study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Antenatally detected arrhythmias allowed prompt and early referral to our tertiary care center, preventing further deterioration. This study has shown that a high percentage of ECG detected arrhythmias have significant echocardiography and Doppler findings, similar to a study by Mene-Afejuku et al (12). Thus, also warranting that all detected arrhythmias be advised for an echocardiography and colour Doppler study.…”
Section: Discussionsupporting
confidence: 89%
“…Although the diagnostic yield is low in the pediatric age group, Holter monitoring enables cumulative evaluation of heart rhythm and rhythm variability, which is important in diagnosing silent arrhythmias in high risk groups (abnormal heart in cardiomyopathies or postoperative heart) (12,13). Early detection and management play a vital key to survival (14).…”
Section: Svoa Paediatricsmentioning
confidence: 99%
“…This review identified underlying etiologies of SCA/SCD and ventricular arrhythmias in SSA, with hypertensive heart disease, coronary disease, cardiomyopathy, including peripartum cardiomyopathy, and valvular heart disease, especially rheumatic heart disease being the most common causes of SCA/SCD among adults [ 61 64 67 69 71 72 73 90 ]. Others include malignant arrhythmogenic inherited diseases [ 74 75 76 77 78 79 80 81 84 85 86 87 88 102 103 104 ], pericarditis [ 92 ], endemic parasitic infections [ 9 93 ], pulmonary embolism [ 62 91 ], endomyocardial fibrosis [ 95 ], congenital heart disease [ 96 ], pulmonary embolism [ 62 91 ], pulmonary hypertension [ 61 ], and aortic dissection/rupture [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified hypertensive heart disease, coronary disease, cardiomyopathy, and valvular heart disease, especially rheumatic heart disease, in heterogeneous orders, as the most common causes of SCA/SCD among adults in SSA [61,64,67,69,[71][72][73], while malaria was the prominent cause among the pediat- Cases of hypertrophic cardiomyopathy have been reported in Black Africans [74,75]. Little was known about arrhythmogenic right ventricular cardiomyopathy (ARVC) in SSA, but registry data from South Africa revealed similar clinical presentation and an annual SCA/SCD rate comparable to other large registries from the Western World [76,77].…”
Section: Reported Underlying Etiologies Of Sca/scd and Ventricular Armentioning
confidence: 99%
See 1 more Smart Citation